Twelve-month outcomes of excisional goniotomy using the Kahook Dual Blade(®) in eyes with angle-closure glaucoma - Dorairaj, Syril (Clin Ophthalmol, 2019)
PURPOSE: To characterize clinical outcomes following Kahook Dual Blade(®) (KDB)-assisted goniosynechialysis and excisional goniotomy combined with phacoemulsification in eyes with angle-closure glaucoma and cataract. SETTING: Two clinical practices. METHODS: In this retrospective analysis of existing health records, data were collected from 42 eyes of 24 subjects from preoperative, operative, and postoperative encounters through 12 months of follow-up. Outcomes included changes in mean IOP, IOP-lowering medications, and logMAR best-corrected visual acuity (BCVA), as well as the proportions of patients achieving IOP reductions ≥20%, IOP ≤18 mmHg, and a reduction of ≥1 medication. RESULTS: Preoperative, mean (standard error) IOP was 25.5 (0.7) mmHg and at Month 12 was reduced by 12.3 (0.73) mmHg (−47.2%; p<0.0001). The mean number of IOP-lowering medications used was 2.3 (0.1) preoperatively and was reduced at Month 12 by 2.2 (0.12) (−91.7%; p<0.0001). At Month 12, 92.9% of eyes achieved IOP ≤18 mmHg, 100% achieved IOP reduction of ≥20%, 95.2% required ≥1 fewer medications for IOP control, and 85.7% (36/42) were medication-free. Mean LogMAR BCVA improved from 0.547 (0.06) at baseline to 0.159 (0.07) at Month 12. CONCLUSION: KDB-assisted goniosynechialysis and excisional goniotomy at the time of phacoemulsification safely provide significant reductions in both IOP and IOP-lowering medication burden in eyes with angle-closure glaucoma, while simultaneously improving visual acuity.